Equitability or proportionality?: local-level portfolio allocation in Germany - Ecker, Alejandro; Gross, Martin (West European politics, 2024)
This study addresses a fundamental question in democratic systems: how do government parties allocate executive portfolios? While extensive research has tackled this question at the national and regional levels, there is a notable gap in understanding the local level. This study addresses this issue by analysing portfolio allocation at the local level in Germany. Both the quantitative aspect, focusing on the number of portfolios, and the qualitative aspect, examining the distribution across policy fields, are explored. The findings reveal a highly politicised approach to portfolio allocation at the local level. Local political actors prioritise proportional allocations over equitable distributions. Additionally, local parties seek portfolios aligned to policy issue areas that feature prominently in their election manifestos. This study sheds light on the intricacies of local-level portfolio distribution, contributing to a more comprehensive understanding of local democratic governance.
Online veröffentlicht: 8. November 2024
Gesehen am 21.05.2025